ТЕОРЕТИКО-ПРАКТИЧЕСКИЕ ОСНОВЫ УПРАВЛЕНИЯ КАЧЕСТВОМ ОБРАЗОВАНИЯ В ВУЗАХ - Саидова, Ф.Б. (SCIENCE and SOCIETY, 2016)
The article is about issues related to the management of the quality of education at the higher educational establishments. The author pays attention to the importance of the organization of the theoretical and practical foundation to manage the quality of education at the present stage.